Software Process Customization and Improvement Tool - Taneja, Harsh (My University, 2012)
Software Process Improvement (SPI) has now become a milestone. Every small, medium or large organization want to achieve it. There are many organizations those want to improve the processes but in their own way. Therefore SPI is now moving towards Process Customization, that is they want to select processes with respect to their budget, time and resources. Different advances have been made in the development of software process improvement (SPI) standards and models, e.g. capability maturity model (CMM), CMMI, and ISO‟s SPICE. However, these advances have not been matched by equal advances in the adoption of these standards and models in software development which has resulted in limited success for many SPI efforts. The current problem with SPI is not a lack of standard or model, but rather a lack of an effective strategy to successfully implement these standards or models. The importance of SPI implementation demands that it be recognized as a complex process in its own right and that organizations should determine their SPI implementation maturity through an organized set of activities and process areas. In the thesis, much attention has been paid to „„what activities to implement‟‟ instead of „„how to implement these activities”. The Software Process Customization and Improvement (SPCI) tool is developed in order to cater the needs of Software Industry w.r.t their available resources. Process and related activities are identified from various available models and grouped into various categories to make customized software available to organizations. Now, they can select the proper set of activities according to their need and budget from the tool developed and can proceed to next level with maturity. Thus Software Development Process being followed is improved to enhance the quality of product time to time.
The Software Process Customization and Improvement (SPCI) tool is developed in order to cater the needs of Software Industry w.r.t their available resources. Now, they can select the proper set of activities according to their need and budget from the tool developed and can proceed to next level with maturity. Thus Software Development Process being followed is improved to enhance the quality of product time to time.
Keywords: Software Process Customization; Software Process Improvement; Software Process Customization Tool; SPI in Small and Medium scale Enterprises